2011
DOI: 10.1103/physrevb.83.081101
|View full text |Cite|
|
Sign up to set email alerts
|

Band convergence and linearization error correction of all-electronGWcalculations: The extreme case of zinc oxide

Abstract: Recently, Shih et al. [Phys. Rev. Lett. 105, 146401 (2010)] published a theoretical band gap for wurtzite ZnO, calculated with the non-self-consistent GW approximation, that agreed surprisingly well with experiment while deviating strongly from previous studies. They showed that a very large number of empty bands is necessary to converge the gap. We reexamine the GW calculation with the full-potential linearized augmented-plane-wave method and find that even with 3000 bands the band gap is not completely conve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
97
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(107 citation statements)
references
References 22 publications
(41 reference statements)
10
97
0
Order By: Relevance
“…It can be seen that, as l max goes from l = 0 to l = 1, the error of the self-energy or the quasiparticle energy drastically reduces by around 0.6 eV, and by increasing l max , the self-energy decreases monotonically. The self-energy converges slowly with respect to l max , which is reminiscent of a similar problem in GW calculations associated with summing over unoccupied states [11][12][13]. Our estimated value for l max → ∞ by extrapolation is 0.02 ± 0.01 eV.…”
Section: -2mentioning
confidence: 68%
See 1 more Smart Citation
“…It can be seen that, as l max goes from l = 0 to l = 1, the error of the self-energy or the quasiparticle energy drastically reduces by around 0.6 eV, and by increasing l max , the self-energy decreases monotonically. The self-energy converges slowly with respect to l max , which is reminiscent of a similar problem in GW calculations associated with summing over unoccupied states [11][12][13]. Our estimated value for l max → ∞ by extrapolation is 0.02 ± 0.01 eV.…”
Section: -2mentioning
confidence: 68%
“…One possible reason for this failure could be that, in the G 0 W 0 approximation or RPA, the polarization function contains the unphysical self-screening effect where an electron shields the field produced by itself [10]. In order to improve the theory, careful analysis is required to identify the shortcomings of the GW approximation, but because of the complexity of the GW calculation due to the nonlocality and frequency dependence of the self-energy, it is usually difficult to analyze the self-energy in detail and sometimes it is even more difficult to get converged results [11][12][13]. The hydrogen atom is one of the few real systems where the exact eigenfunctions and energies are known analytically, and it is an ideal system for studying the self-screening problem because, for the 1s state, the error arises entirely from the correlation part of the self-energy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that a large number of bands is necessary to obtain properly converged results in earlier one-shot G 0 W 0 calculations [51][52][53]. We speculate that the deviations to Ref.…”
Section: B Electronic Propertiesmentioning
confidence: 68%
“…Parameters controlling the calculations include the number of bands [51][52][53], the exchange-correlation potential for the starting wave function [22] as well as the use of approximate mod- …”
Section: B Electronic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation